Immune Checkpoint Inhibitor Associated Hepatotoxicity in Primary Liver Cancer Versus Other Cancers: A Systematic Review and Meta‐Analysis - Fu, Jianyang; Li, Wang-Zhong; McGrath, Nicole A.; Lai, Chunwei Walter; Brar, Gagandeep; Xiang, Yan-Qun; Xie, Changqing (Frontiers in Oncology, 2021)
Background Overall risks of hepatotoxicity with immune checkpoint inhibitors (ICIs) have yet to be compared in primary liver cancers to other solid tumors. Methods We reviewed data from the PubMed, Embase, and Scopus databases, and assessed the risk of hepatotoxicity associated with ICIs. Results A total of 117 trials were eligible for the meta‐analysis, including 7 trials with primary liver cancers. The most common hepatotoxicity was ALT elevation (incidence of all grade 5.29%, 95% CI 4.52-6.20) and AST elevation (incidence of all grade 5.88%, 95% CI 4.96-6.97). The incidence of all grade ALT and AST elevation was 6.01% and 6.84% for anti-PD‐1 (95% CI 5.04-7.18/5.69-8.25) and 3.60% and 3.72% for anti-PD-L1 (95% CI 2.72-4.76/2.82-4.94; p< 0.001/p<0.001). The incidence of ≥ grade 3 ALT and AST elevation was 1.54% and 1.48% for anti-PD‐1 (95% CI 1.19-1.58/1.07-2.04) and 1.03% and 1.08% for anti-PD-L1 (95% CI 0.71-1.51/0.80-1.45; p= 0.002/p<0.001). The incidence of all grade ALT and AST elevation was 13.3% and 14.2% in primary liver cancers (95% CI 11.1-16.0 and 9.93-20.36) vs. 4.92% and 5.38% in other solid tumors (95% CI 4.21-5.76 and 4.52-5.76 in other solid tumors; p <0.001/p<0.001). Conclusion Our study indicates that anti-PD-1 is associated with a higher risk of all‐ and high‐grade hepatotoxicity compared to anti-PD-L1, and primary liver cancers are associated with a higher risk of all‐ and high‐grade hepatotoxicity compared to other solid tumors.